Total Dairy Consumption Is Not Associated With Likelihood of a First Clinical Diagnosis of Central Nervous System Demyelination - Dieu, Dao Ying Rachel; Dunlop, Eleanor; Daly, Alison; Lucas, Robyn M.; Probst, Yasmine; Black, Lucinda J. (Frontiers in Neurology, 2022)
Background The evidence associating consumption of dairy products and risk of MS is contradictory and inconclusive. Objective To test associations between dairy consumption and the likelihood of a first clinical diagnosis of central nervous system demyelination (FCD), a common precursor to MS. Methods We used data from the 2003–2006 Ausimmune Study, a population-based Australian, multicentre, matched case-control study (272 cases, 519 controls). Total dairy consumption (servings/day) was calculated by summing consumption of milk, cheese and yogurt. Covariate-adjusted treatment effects using augmented inverse probability weighting was used to test for associations with FCD. We conducted sensitivity analyses in the subset of participants who had had a classic first demyelinating event (FDE), defined as a single, first episode of symptoms suggestive of CNS demyelination. Results There were no statistically significant associations between total dairy consumption (per one serving/day) and FCD (adjusted OR 1.00; 95% CI 0.93, 1.07; p = 0.979). However, yogurt consumption (vs. no yogurt consumption) was associated with an 11% decreased likelihood of FDE (adjusted OR 0.89; 95% CI 0.89, 0.79; p = 0.046). Conclusion While total dairy consumption was not associated with FCD in this Australian case-control study, yogurt consumption was associated with reduced likelihood of FDE.